Eplerenone for chronic central serous chorioretinopathy in patients with active, previously untreated disease for more than 4 months (VICI): a randomised, double-blind, placebo-controlled trial. Issue 10220 (25th January 2020) - Lotery, Andrew; Sivaprasad, Sobha; O'Connell, Abby; Harris, Rosie A; Culliford, Lucy; Ellis, Lucy; Cree, Angela; Madhusudhan, Savita; Behar-Cohen, Francine; Chakravarthy, Usha; Peto, Tunde; Rogers, Chris A; et al.
Summary: Background: In chronic central serous chorioretinopathy (CSCR), fluid accumulates in the subretinal space. CSCR is a common visually disabling condition that develops in individuals up to 60 years of age, and there is no definitive treatment. Previous research suggests the mineralocorticoid receptor antagonist, eplerenone, is effective for treating CSCR; however, this drug is not licensed for the treatment of patients with CSCR. We aimed to evaluate whether eplerenone was superior to placebo in terms of improving visual acuity in patients with chronic CSCR. Methods: This randomised, double-blind, parallel-group, multicentre placebo-controlled trial was done at 22 hospitals in the UK. Participants were eligible if they were aged 18–60 years and had had treatment-naive CSCR for 4 months or more. Patients were randomly assigned (1:1) to either the eplerenone or the placebo group by a trial statistician through a password-protected system online. Allocation was stratified by best-corrected visual acuity (BCVA) and hospital. Patients were given either oral eplerenone (25 mg/day for 1 week, increasing to 50 mg/day for up to 12 months) plus usual care or placebo plus usual care for up to 12 months. All participants, care teams, outcome assessors, pharmacists, and members of the trial management group were masked to the treatment allocation. The primary outcome was BCVA, measured as letters read, at 12 months. All outcomes apart from safety were analysed on a modified intention-to-treat basis (participants who withdrew consent without contributing a post-randomisation BCVA measurement were excluded from the primary analysis population and from most secondary analysis populations). The trial is registered with ISRCTN, ISRCTN92746680, and is completed. Findings: Between Jan 11, 2017, and Feb 22, 2018, we enrolled and randomly assigned 114 patients to receive either eplerenone (n=57) or placebo (n=57). Three participants in the placebo group withdrew consent without contributing a post-randomisation BCVA measurement and were excluded from the primary outcome analysis population. All patients from the eplerenone group and 54 patients from the placebo group were included in the primary outcome. Modelled mean BCVA at 12 months was 79·5 letters (SD 4·5) in the placebo group and 80·4 letters (4·6) in the eplerenone group, with an adjusted estimated mean difference of 1·73 letters (95% CI −1·12 to 4·57; p=0·24) at 12 months. Hyperkalaemia occurred in eight (14%) patients in each group. No serious adverse events were reported in the eplerenone group and three unrelated serious adverse events were reported in the placebo group (myocardial infarction [anticipated], diverticulitis [unanticipated], and metabolic surgery [unanticipated]). Interpretation: Eplerenone was not superior to placebo for improving BCVA in people with chronic CSCR after 12 months of treatment. Ophthalmologists who currently prescribe eplerenone for CSCR should discontinue this practice. Funding: Efficacy and Mechanism Evaluation Programme, and National Institute for Health Research and Social Care.